Analysis of the Influence of Product Price and Quality on Consumer Purchasing Decisions (Case study: Economics Study Program Students, Faculty of Economics, Medan State University) - Gaol, Rianto Irvandinata Lumban; Hidayat, Nasrullah; Tampubolon, Anecya; Gultom, Grace Amelia Margareth (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2024)
Competition in the industry is getting tougher, so companies must offer more value to attract consumer purchasing power. Consumer purchasing decisions are influenced by various factors, including price and product quality. This research aims to analyze the influence of price and product quality on consumer purchasing decisions. The research methods used include observation, literature study, and questionnaires. The research objects were 41 students of the Economics Study Program, Faculty of Economics, Medan State University who filled out a questionnaire. The research results showed that 53.7% of respondents stated that product price had a big influence on purchasing decisions. As many as 53.7% of respondents tend to choose cheaper products, and 56.1% consider discount promotions to be very important. In addition, 58.3% of respondents compared product prices with online shopping platforms to get the cheapest price. Meanwhile, 58.5% of respondents stated that product quality greatly influenced their purchasing decisions. As many as 63.4% of respondents were willing to pay more for quality products, and 87.8% of respondents preferred products with higher prices but better quality. Based on the results of this research, it can be concluded that product price and quality have a significant influence on consumer purchasing decisions.